2016
DOI: 10.5114/aoms.2016.62922
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of inhomogeneities of repolarization in patients with psoriasis vulgaris

Abstract: IntroductionThe arrhythmia potential has not been investigated adequately in psoriatic patients. In this study, we assessed the ventricular repolarization dispersion, using the Tp-e interval and the Tp-e/QT ratio, and investigated the association with inflammation.Material and methodsSeventy-one psoriasis vulgaris patients and 70 age- and gender-matched healthy individuals were enrolled in the study. The severity of the disease was calculated using Psoriasis Area and Severity Index scoring. The QTd was defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…A recent study showed that QTd was significantly higher in patients with psoriasis ( 27 ). Also, Soylu et al ( 28 ) recently reported that QT and QTc intervals were increased in patients with psoriasis compared with control subjects, similar to the results of our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A recent study showed that QTd was significantly higher in patients with psoriasis ( 27 ). Also, Soylu et al ( 28 ) recently reported that QT and QTc intervals were increased in patients with psoriasis compared with control subjects, similar to the results of our study.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have indicated that some chronic inflammatory diseases, including rheumatoid arthritis and ankylosing spondylitis, are associated with an increased Tp-e interval and Tp-e/QT ratio ( 30 , 31 ). Recently, Soylu et al ( 28 ) reported that Tp-e and Tp-ec intervals and the Tp-e/QT ratio were higher in patients with psoriasis. Likewise, in our study, we found that Tp-e and Tp-ec intervals and the Tp-e/QT ratio were increased in patients with psoriasis compared with control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that the Tp-e interval and Tp-e/QT ratio can be used as an index of transmural dispersion of repolarisation. [10][11][12] In our study, we demonstrated that QTc max, QTc dis, Tp-e interval, and Tp-e/QTc max ratio were significantly prolonged in psoriasis patients (Table 2). Also, we found that Pdis had a positive correlation with QTc max (Table 3).…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, low serum concentration of n-3 PUFA in psoriasis with higher PASI, found in our group of PsA patients, may be associated with enhanced inflammation and it may play a role in the development of comorbidity. Several epidemiological studies have confirmed a strong association of moderate to severe psoriasis with cardiometabolic disorders including obesity, type 2 diabetes, dyslipidemia and metabolic syndrome, hypertension and arrhythmia [38, 39]. A diet enriched in n-3 PUFA ameliorates metabolic markers and clinical outcome in psoriatic patients with obesity [36].…”
Section: Discussionmentioning
confidence: 99%